A Chronicle of Hybrid Atrial Fibrillation Ablation Therapy: From Cox Maze to Convergent - Riyaz A Kaba; Omar Ahmed; Elijah Behr; Aziz Momin (Arrhythmia & Electrophysiology Review)
The burden of AF is increasing in prevalence and healthcare resource usage in the UK and worldwide. It can result in impaired quality of life for affected patients, as well as increased risk of stroke, heart failure and mortality. A holistic, integrated approach to AF management is recommended, which may include a focus on reducing risk factors and on medical management with anticoagulation and anti-arrhythmic drugs. There are also various ablation strategies that may be considered when anti-arrhythmic drugs fail to alleviate symptoms and reduce AF burden. These ablation techniques range from standalone percutaneous endocardial catheter ablation to open surgical ablation procedures concomitant with cardiac surgery. More recently, hybrid ablation that combines aspects of both surgical and electrophysiologically targeted ablation has been described. This article reviews the evolution of ablation strategies, beginning with the origin of the Cox maze IV procedure and continuing to the recent hybrid convergent approach, and provides a summary of the associated outcomes.